Atenção nutricional ambulatorial à criança e ao adolescente: fatores que influenciam no seguimento - Cordeiro, Eslen Giovana da Silva (2025)
ntroduction: The process of child growth and development is considered complex and multifactorial and is influenced by genetics, hormones, psychosocial and nutritional factors. Early nutritional monitoring, aimed at the adoption of healthy eating habits in childhood, is necessary, considering its role in preventing nutritional problems in the different stages of life. Adherence to the proposed therapy during nutritional monitoring is influenced by different factors and its understanding by professionals can lead to improvements in treatment adherence. Objective: To identify the factors that influence the maintenance and/or abandonment of nutritional monitoring, as well as the effect of following up or abandoning it for children and adolescents in a public specialized outpatient service. Methodology: A study with a quantitative and qualitative approach, developed in two stages. The first was a quantitative, exploratory analytical retrospective cohort, whose data was obtained from medical records, relating to the care of children and adolescents who began follow-up between June 2019 and June 2022, and who were discharged or abandoned follow-up at a nutrition outpatient clinic, belonging to a specialized secondary health care service in the municipality of Cascavel-PR. The second stage was qualitative and participants were selected by simple random sampling from the medical records assessed in the first stage. Semi-structured face-to-face interviews were carried out. The participants were children and adolescents and their respective guardians who had attended at least one outpatient clinic. At the same time, an anthropometric assessment was carried out and the food consumption of the participating children and adolescents was evaluated, using food surveys already used in the aforementioned clinic. Descriptive analysis of categorical variables was carried out using absolute and relative frequencies and numerical variables using measures of central tendency (median) and dispersion (interquartile range), indicated according to their distribution using the Shapiro-Wilk Normality Test. Poisson regression with robust variance was used to verify the association between the predictor variables (sociodemographic, clinical and anthropometric) and the outcome (abandonment of nutritional follow-up). The qualitative data was subjected to inductive thematic content analysis. Results: There was a high frequency (84.3%) of abandonment of nutritional monitoring, which was associated with risk factors such as dyslipidemia, obesity and severe childhood obesity. The following were identified as protective factors: attendance at appointments, family history of chronic diseases and obesity, nutritional status of marked thinness and age group. Organizational aspects related to the health service and individual aspects related to the child/adolescent and their family environment were recognized as challenges to maintaining nutritional follow-up. Despite the challenges and the high frequency of abandonment of follow-up, satisfactory changes in food consumption were observed, even when there was no nutritional follow-up until discharge. Conclusion: The study showed that the maintenance and/or withdrawal of nutritional monitoring by children and adolescents is multifactorial and involves aspects related to the individual, the family and the health service, thus highlighting the need for interventions focused on this public in a comprehensive manner.